2019
DOI: 10.1021/acsphotonics.9b00523
|View full text |Cite
|
Sign up to set email alerts
|

Achromatic Varifocal Metalens for the Visible Spectrum

Abstract: Metasurface optics provide an ultrathin alternative to conventional refractive lenses. A present challenge is in realizing metasurfaces that exhibit tunable optical properties and achromatic behavior across the visible spectrum. Here, we report the design, fabrication, and characterization of metasurface lenses (“metalenses”) that use asymmetric titanium dioxide (TiO2) nanostructures to induce a polarization-dependent optical response. By rotating the polarization of linearly polarized input light, the focal l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 45 publications
0
52
0
Order By: Relevance
“…Moreover, our metasurface based on beam shaper can be directly integrated with fiber optic probes and microfluidic devices [ 60 , 62 ]. Moreover, a tunable metasurface based on beam shaper can be designed to adjust trapping potentials along the axial direction [ 63 , 64 , 65 ]. Our technique is not limited only to Airy beams, and other exotic light beams can be created from a metasurface with different operation wavelengths, without any additional optical components.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our metasurface based on beam shaper can be directly integrated with fiber optic probes and microfluidic devices [ 60 , 62 ]. Moreover, a tunable metasurface based on beam shaper can be designed to adjust trapping potentials along the axial direction [ 63 , 64 , 65 ]. Our technique is not limited only to Airy beams, and other exotic light beams can be created from a metasurface with different operation wavelengths, without any additional optical components.…”
Section: Discussionmentioning
confidence: 99%
“…For the continuous variation of the focal length, Aiello et al. [ 133 ] demonstrated a varifocal meta‐lens based on the rotational polarization of linearly polarized incident light, as shown in Figure 11b. The focal length can be tuned from 220 to 550 µm.…”
Section: Functionalitiesmentioning
confidence: 99%
“…Reproduced with permission. [ 133 ] Copyright 2019, American Chemical Society. c) Unit cell structure for electrically modulated meta‐lens combined with TN LCs.…”
Section: Functionalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally, metasurfaces have diverse potential and have exhibited various applications, stemming from their designs with large degree of freedom [ 14 , 15 , 16 ]. Most of metasurfaces intended to manipulate light waves for particular purposes such as focusing [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ], polarization/phase control [ 24 , 25 , 26 , 27 , 28 , 29 ], perfect light absorption [ 30 , 31 , 32 , 33 , 34 , 35 ], and so on. The application of metasurfaces for FL enhancement has been tried in numerous studies; only a very small portion of the studies exceptionally reported prominent success in the very large FL-intensity enhancement more than 1000-fold to reference non-enhancing substrates [ 10 , 11 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%